Implementation of Smart City Policy in Creative Economy Development in Boyolali Regency - Dhita Evany Aristyawati; Nunik Nurhayati (Universitas Muhammadiyah Surakarta, 2025)
This study examines the implementation of the Smart City concept in the development of the creative economy in Boyolali Regency, which is supported by Regional Regulation Number 12 of 2022 concerning the Implementation of Smart Regency. The creative economy is a main pillar in national development, and local governments play an important role in creating an ecosystem that supports it. Boyolali adopts Smart City with a focus on a technology-based economy, increasing the value of its individuals, innovative governance structures, and a sustainable environment. This implementation includes the development of digital infrastructure, MSME training, and technology-based public services. This study also uses a juridical-empirical method to analyze the application of legal regulations in society. The results of the study show that Boyolali Regency has taken significant steps, such as the construction of the Smart City Center Building and the provision of public WiFi access. In addition, the government is active in providing socialization and training to MSMEs to utilize technology in product promotion. The key to the success of Smart City in Boyolali is active community participation and collaboration between the government and various parties. Despite challenges such as the digital divide and limited human resources, Boyolali has outstanding potential to develop a technology-based creative economy industry and become a model of a highly competitive smart city.